CEO CHARACTERISTICS AND NET OPERATING WORKING CAPITAL - Rizka Dita Zhafira; Rahmat Setiawan (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2026)
Introduction: This study examines the effect of CEO characteristics, specifically CEO age, tenure, and gender on net operating working capital (NOWC) in non-financial firms listed on the Indonesia Stock Exchange. Methods: Using panel data from 320 firms over the period 2018-2025 (2,176 firm-year observations), this study employs linear regression to analyze the impact of managerial attributes on working capital policy. Results: The results show that CEO age, tenure, and gender have a positive and significant effect on NOWC. Firm size and gross profit margin positively influence NOWC, while sales growth and market share have a negative and significant effect. Conclusion and suggestion: These findings support Upper Echelons Theory, highlighting the role of managerial characteristics in shaping corporate financial decisions. This study contributes empirical evidence from an emerging market context and provides practical insights for aligning working capital strategies with CEO profiles.